Assessments of the ecological and health risks of potentially toxic metals in the topsoils of different land uses: a case study in Peninsular Malaysia - Yap, Chee Kong; Chew, Weiyun; Al-Mutairi, Khalid Awadh; Nulit, Rosimah; Ibrahim, Mohd. Hafiz; Wong, Koe Wei; Bakhtiari, Alireza Riyahi; Sharifinia, Moslem; Ismail, Mohamad Saupi; Leong, Wah June; Tan, Wen Siang; Cheng, Wan Hee; et al. (MDPI, 2022)
Human activities due to different land uses are being studied widely in many countries. This study aimed to determine the ecological risks and human health risk assessments (HHRA) of Cd, Pb, Ni, Cu, and Zn in the topsoils of six land uses in Peninsular Malaysia. The ranges of the potentially toxic metals (PTMs) in the soils (mg/kg, dry weight) of this study were 0.24–12.43 for Cd (mean: 1.94), 4.66–2363 for Cu (mean: 228), 2576–116,344 for Fe (mean: 32,618), 2.38–75.67 for Ni (mean: 16.04), 7.22–969 for Pb (mean: 115) and 11.03–3820 for Zn (mean: 512). For the ecological risk assessments, the potential ecological risk index (PERI) for single metals indicated that the severity of pollution of the five metals decreased in the following sequence: Cd > Cu > Pb > Zn > Ni. It was found that industry, landfill, rubbish heap, and mining areas were categorized as “very high ecological risk”. For HHRA, the land uses of industry, landfill and rubbish heap were found to have higher hazard quotient (HQ) values for the three pathways (with the order: ingestion > dermal contact > inhalation ingestion) of the five metals for children and adults, when compared to the mining, plantation, and residential areas. The values for both the non-carcinogenic (Cd, Cu, Ni, and Zn), and carcinogenic risks (CR) for inhalation (Cd and Ni) obtained for children and adults in this study showed no serious adverse health impacts on their health. However, of public concern, the hazard index (HI), for Pb of children at the landfill (L-3) and the rubbish heap (RH-3) sites exceeded 1.0, indicating non-carcinogenic risk (NCR) for children. Therefore, these PERI and HHRA results provided fundamental data for PTMs pollution mitigation and environmental management in areas of different land uses in Peninsular Malaysia.